1991
DOI: 10.1093/oxfordjournals.aje.a116184
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Possible Transmission of Amantadine-resistant Viruses during Nursing Home Outbreaks of Influenza A (H3N2)

Abstract: Outbreaks of influenza A (H3N2, A/Shanghai/11/87-like) occurred in two partially (60% and 79%) vaccinated nursing home populations in January 1988. A retrospective cohort study using chart review was designed to assess the effectiveness of influenza vaccination and amantadine prophylaxis (100 mg per day) in controlling the outbreaks and to determine the amantadine susceptibility of influenza viruses isolated from case-patients. The point estimate of vaccine efficacy in preventing influenza-like illness was -33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(64 citation statements)
references
References 34 publications
2
61
0
1
Order By: Relevance
“…Up to approximately one-third of the patients shed resistant viruses when amantadine or rimantadine is used for therapy (7,10,12). Transmission of drug-resistant viruses to close, sensitive contacts in families and other semi-closed settings has been described (5,6,9,12,14,(20)(21)(22). Thus, the results indicate that resistant viruses can occur quickly and be transmitted when used in an outbreak situation at nursing homes when amantadine is administered either for neurological indications or influenza treatment, as reported previously (9).…”
Section: Resultsmentioning
confidence: 99%
“…Up to approximately one-third of the patients shed resistant viruses when amantadine or rimantadine is used for therapy (7,10,12). Transmission of drug-resistant viruses to close, sensitive contacts in families and other semi-closed settings has been described (5,6,9,12,14,(20)(21)(22). Thus, the results indicate that resistant viruses can occur quickly and be transmitted when used in an outbreak situation at nursing homes when amantadine is administered either for neurological indications or influenza treatment, as reported previously (9).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many investigators have revealed the appearance of amantadine-resistant viruses in nursing homes or household settings where prophylactic or therapeutic use of the drug occurs (8,12,14). Up to approximately one-third of patients may shed resistant viruses when amantadine or rimantadine is used for therapy (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that single nucleotide changes leading to corresponding amino acid substitutions of one of four critical sites-amino acids 26, 27, 30, and 31-in the transmembrane region of the M2 protein confer resistance (6,11,13,16). In the clinical field, we can detect actual resistant viruses by several methods, such as enzyme-linked immunosorbent assay (1,9,12,14,18), plaque reduction (7), TCID 50 /0.2-ml titration (15), sequencing analysis (1, 9, 12-15), or PCR-RFLP methods (6,13).…”
Section: Discussionmentioning
confidence: 99%
“…3b do not correlate with published experiences in using this strategy of mass chemoprophylaxis (with or without treatment of ill persons). Termination of the outbreak is usually found and the number of clinical prophylaxis failures is usually very low, even in studies reporting the emergence of resistant variants [2,3,5]. In such circumstances, clinical influenza has developed in 4 -10% of patients receiving prophylaxis and proven prophylaxis failures due to resistant virus has occuired in 2 -3% of prophylaxis recipients.…”
Section: -1mentioning
confidence: 99%